EXPLORATION OF RHIZOPORA MANGROVE PLANTS AS FUNCTIONAL FOOD COMPOUNDS FROM THE CUKU NYINYI ECOTOURISM AREA, SIDODADI VILLAGE PESAWARAN REGENCY, LAMPUNG PROVINCE - Oktaf Rina; Anggun Rusyantia; Ajis Purnomo; Andi Sofiyan (Bajang Institute, 2024)
This activity was empowerment community programme assisted by CSR PT. Bukit Asam Tbk Pelabuhan Tarahan Lampung. This research is a series of activities in an effort to preserve Mangrove plantation forests in Pesawaran Regency, Lampung province in collaboration with CSR PT. Bukit Asam, Tarahan Pelabuhan Panjang. The specific aim is to explore and screen Mangrove plants that have the potential to be used as food. There were 2 (two) types of Mangrove plants studied, namely the Mangrove species Rhizopora apiculata and Rhizophora mucronata. The first step of the research was to carry out phytochemical screening to identify chemical content and bioactive compounds using qualitative methods, and the bioactive compounds identified were flavonoids, saponins, tannins, tripertenoids and steroids as well as phenolic compounds. The third step is to test the main components of chemical compounds using proximate analysis which include tests for water content, ash content, total fat, protein and carbohydrates as well as crude fiber components. Chemical content test results of proximate analysis of mangrove fruit Rhizopora apiculata and Rhizophora mucronata for water content; ash content; total fat content; protein content; and carbohydrates each one were 64,99; 3,61;8,11; 0,31; 12,49; 22,95 (%) and 64,25; 3,25; 10,67; 0,74; 1,74, 21,10 (%).The aim of the phytochemical test is to determine the presence of secondary metabolite compounds distributed in plant parts. The research continued with trials of making Rhizopora fruit into food products such as sticks and crackers. The overall sensory test results showed a good level of panelist acceptance of snack food substituted with mangrove flour